Developing specialist CBT supervision training in Scotland using blended learning: challenges and opportunities. (14th October 2016) - Ferguson, Sandra; Harper, Sean; Platz, Shirley; Sloan, Graham; Smith, Katharine
Abstract: NHS Education for Scotland (NES) has developed a suite of training to address the learning and development needs of supervisors of psychological therapies in the National Health Service (NHS) in Scotland and to support quality of evidence-based practice in psychological therapies, in light of the recent expansion in this area of healthcare. In parallel with the structure of the recently developed supervisory competency frameworks, an initial training package addressing generic (cross-modality) supervision competences was supplemented by the development of a training package to meet the specific needs of supervisors of CBT: NES Specialist Supervision Training in CBT (NESSST CBT). A blended learning package was developed, in light of the emerging evidence around the effectiveness of e-learning, to produce a flexible and learner-centred training package. This paper describes the development, delivery and planned evaluation methods of NESSST CBT. Lessons learned during implementation are outlined, along with key challenges regarding the future of supervision training in Scotland and the UK.